Product quality: a study on improving the quality of Agromas product offered by Federal Agricultural Marketing Authority, Melaka / Norehan Md. Ali - Md. Ali, Norehan (Faculty of Business and Management, 2005)
This study of "Product Quality: A Study On Improving The Quality Of Agromas Product Offered By Federal Agricultural Marketing Authority, Melaka In Melaka Tengah" was been done at Lot 73, Jln. Usaha 12, Kaw. Perindustrian, 75450 Ayer Keroh, Melaka. This company was established on 30 September 1965, under the Parliament Act 49, 1965 and Parliament Act 141,1974. As a Government marketing agency, the company functions are to keep close watch, to coordinate and to improve along with expanding the marketing of agricultural goods.